Viral meningoencephalitis in pediatric solid organ or hematopoietic cell transplant recipients: a diagnostic and therapeutic approach - Thomas, Sanya J.; Ouellette, Christopher P. (Frontiers in Pediatrics, 2024)
Neurologic complications, both infectious and non-infectious, are frequent among hematopoietic cell transplant (HCT) and solid organ transplant (SOT) recipients. Up to 46% of HCT and 50% of SOT recipients experience a neurological complication, including cerebrovascular accidents, drug toxicities, as well as infections. Defects in innate, adaptive, and humoral immune function among transplant recipients predispose to opportunistic infections, including central nervous system (CNS) disease. CNS infections remain uncommon overall amongst HCT and SOT recipients, compromising approximately 1% of total cases among adult patients. Given the relatively lower number of pediatric transplant recipients, the incidence of CNS disease amongst in this population remains unknown. Although infections comprise a small percentage of the neurological complications that occur post-transplant, the associated morbidity and mortality in an immunosuppressed state makes it imperative to promptly evaluate and aggressively treat a pediatric transplant patient with suspicion for viral meningoencephalitis. This manuscript guides the reader through a broad infectious and non-infectious diagnostic differential in a transplant recipient presenting with altered mentation and fever and thereafter, elaborates on diagnostics and management of viral meningoencephalitis. Hypothetical SOT and HCT patient cases have also been constructed to illustrate the diagnostic and management process in select viral etiologies. Given the unique risk for various opportunistic viral infections resulting in CNS disease among transplant recipients, the manuscript will provide a contemporary review of the epidemiology, risk factors, diagnosis, and management of viral meningoencephalitis in these patients.